Media Video Sebagai Sarana Informasi Pada Direktorat Jenderal Hak Asasi Manusia - Sunarya, Lusyani; Septiani, Mawar Indah; Setiawan, Agung (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2022)
Information is the result of data processing that can provide knowledge to those who receive it. Currently, a lot of information media has developed rapidly, making it easier for people to find and process the information obtained. The Directorate General of Human Rights is currently under the auspices of the Ministry of Law and Human Rights, which is located at Jl. HR. Rasuna Said Kuningan, South Jakarta. The problem faced at this time is, there is still a lack of media in disseminating information about the Directorate General of Human Rights, the information media which previously were only in the form of print media such as banners, posters, magazines. The methodologies used in this study include: Data collection which consists of Observation, Interview, Literature Study. SWOT Analysis, Media Design using supporting software, namely: Adobe Premiere CC 2019, Adobe Audition CC 2019, Adobe After Effect CC 2019, Adobe Photoshop CC 2019 and Adobe Illustrator CC 2019, Media Production Concept (KPM), namely Pre Production (Pre Production), Production (Production), Post Production (Post Production). The purpose of this research is to assist the Directorate General of Human Rights in delivering complete and updated information to the public. Keywords: Information, Video, Kemenkumham